2015
DOI: 10.1002/jcop.21721
|View full text |Cite
|
Sign up to set email alerts
|

Defining Psychological Empowerment Construct: Analysis of Three Empowerment Scales

Abstract: This study aimed to contribute to the validation of psychological empowerment, which is a combination of sense of control (intrapersonal component), critical awareness of the sociopolitical environment (interactional component), and community involvement (behavioral component). Three scales of empowerment used to evaluate the 3 components were translated into Portuguese, adapted for the Portuguese population, and applied in person, by phone and by e‐mail. Participants were enrolled in or had completed a progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 64 publications
1
31
0
4
Order By: Relevance
“…Given its breadth of application of Zimmerman's model of PE, particularly in the field of community psychology, it is the central model used in the theoretical reflection and the empirical research presented in this article. This study intended to explore current issues in the empowerment theory and measurement based on the concerns raised by Christens (), Peterson (), and Miguel and colleagues (). Peterson () pointed to the need to clarify the nature of PE coming from acknowledging existing evidence of potential misspecification of PE as a reflective construct.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Given its breadth of application of Zimmerman's model of PE, particularly in the field of community psychology, it is the central model used in the theoretical reflection and the empirical research presented in this article. This study intended to explore current issues in the empowerment theory and measurement based on the concerns raised by Christens (), Peterson (), and Miguel and colleagues (). Peterson () pointed to the need to clarify the nature of PE coming from acknowledging existing evidence of potential misspecification of PE as a reflective construct.…”
Section: Discussionmentioning
confidence: 99%
“…Their results revealed weak or modest correlations between measures of PE dimensions (coefficients of .19, .24, and .47). Miguel and colleagues () studied the psychometric properties of PE (three components structure) in a sample of 277 adults in Portugal. They found that measures of cognitive, emotional, and behavioral empowerment components were uncorrelated or very weak correlated (coefficients ranging from .00 to .03).…”
Section: Clarifying the Nature Of Psychological Empowerment As A Highmentioning
confidence: 99%
See 3 more Smart Citations